2016
DOI: 10.1007/978-1-4939-6539-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Deubiquitinating Enzymes and Autophagy in Cancer

Abstract: Maintenance of proper cellular homeostasis requires constant surveillance and precise regulation of intracellular protein content. Protein monitoring and degradation is performed by two distinct pathways in a cell: the autophage-lysosome pathway and the ubiquitin-proteasome pathway. Protein degradation pathways are frequently dysregulated in multiple cancer types and can be both tumor suppressive and tumor promoting. This knowledge has presented the ubiquitin proteasome system (UPS) and autophagy as attractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Another study has shown that the UPS pathway plays an indispensable role in the regulation of mitochondrial energy metabolism by regulating the turnover of several mitochondrial oxidative phosphorylation (OXPHOS) proteins such as the succinate dehydrogenase subunit A (SDHA), the mitochondrial respiratory complex II [63,64]. Findings also indicate a mechanism of crosstalk between the proteasome and autophagy pathway [65][66][67][68][69]. This includes the degradation of synaptosomal-associated protein 29 (SNAP29) and syntaxin 17 (STX17) by the ubiquitin-independent 20S proteasome [70].…”
Section: The Ups and Tumor Metabolismmentioning
confidence: 99%
“…Another study has shown that the UPS pathway plays an indispensable role in the regulation of mitochondrial energy metabolism by regulating the turnover of several mitochondrial oxidative phosphorylation (OXPHOS) proteins such as the succinate dehydrogenase subunit A (SDHA), the mitochondrial respiratory complex II [63,64]. Findings also indicate a mechanism of crosstalk between the proteasome and autophagy pathway [65][66][67][68][69]. This includes the degradation of synaptosomal-associated protein 29 (SNAP29) and syntaxin 17 (STX17) by the ubiquitin-independent 20S proteasome [70].…”
Section: The Ups and Tumor Metabolismmentioning
confidence: 99%
“…TrxR inhibition therefore cannot be the main effector of the oxidative and proteotoxic stress observed with these compounds.Another potential target of these reactive compounds that could result in similar proteotoxic effects is the proteasomal ubiquitin receptor Rpn13. The small molecule inhibitor which selectively targets Rpn13 to inhibit proteasomal degradation closely resembles b-AP15 and VLX1570[342]. This raises the possibility that the observed proteotoxic effects in Paper IV are due to inhibition of ubiquitin binding to the proteasome.…”
mentioning
confidence: 97%
“…In tumors, autophagy is believed to promote tumor growth and progression by helping cells adapt to the harsh tumor microenvironment. Therefore, some autophagy inhibitors, such as hydroxychloroquine (HCQ), are used in anti-cancer treatment strategies [16]. Recent studies have found that IU1 could induce autophagy in cancer cells [15].…”
Section: Discussionmentioning
confidence: 99%
“…We propose that IU1 regulates MDM2 protein levels by a post-translational mechanism. The proteasome system UPS and the autophagy system, are the two primary pathways in intracellular protein degradation 16 - 18 . Here, we showed that IU1 treatment promoted UPS function and activated autophagy.…”
Section: Introductionmentioning
confidence: 99%